Effects of Docosahexanoic Acid on Gut Microbiota and Fecal Metabolites in HIV-Infected Patients With Neurocognitive Impairment: A 6-Month Randomized, Double-Blind, Placebo-Controlled Trial - Dong, Ruihua; Lin, Haijiang; Ding, Yingying; Chen, Xiaoxiao; Shi, Ruizi; Yuan, Shiying; Li, Jing; Zhu, Bowen; Xu, Xiaohui; Shen, Weiwei; Wang, Keran; Ding, Ding; et al. (Frontiers in Nutrition, 2022)
Neurocognitive impairment (NCI) and gut microbiota dysbiosis is prevalent in patients with HIV infection. Docosahexanoic acid (DHA) supplementation may alleviate multiple neurocognitive diseases symptoms and play important roles in regulating gut microbiota. However, it is not known whether docosahexanoic acid (DHA) algae oil supplement can alleviate neurocognitive impairment (NCI) and regulate gut microbiota and faecal metabolites. A randomized, double-blind, placebo-controlled trial was performed on 68 HIV-infected patients with NCI. Participants were randomized to receive 3.15 g daily DHA algae oil supplement or placebo for 6 months. We collected blood and faecal samples from these patients before and after the trial. Mini mental state examination (MMSE) and Neuropsychological tests (NP tests) were administered to assess cognitive status of participants. The influence of DHA algae oil on the gut microbiota, faecal metabolomics, plasma proinflammatory and oxidative stress factors were also investigated. There were no significant changes in NCI according to GDS (global diagnosis score) and MMSE score within the two groups, while patients receiving DHA had improvement in several blood lipids, pro-inflammatory and oxidative stress factors. The DHA supplement increased α-diversity indexes, increased abundances of Blautia, Bifidobacterium, Dorea, Lactobacillus, Faecalibacterium, Fusobacterium and Agathobacter and decreased abundances of Bacteroides and Prevotella_9. Furthermore, DHA supplement was correlated with improved faecal lipid metabolites as indicated by ceramides, bile acids, glycerophospholipids. In addition, the DHA supplement was associated with altered cholesterol metabolism and purine metabolism pathways. Daily supplement of DHA algae oil for 6 months has shown to promote favorable transformations in gut microbiota, profiles of faecal metabolomic and factors responsible for proinﬂammatory and oxidative stress, which might be beneficial for the prognosis of HIV-infected patients with NCI in the long-term.